Software agents, agent systems and their applications - Software agents, agent systems and their applications / [edited by] Mohammad Essaidi, Maria Ganzha, Marcin Paprzycki; Essaaidi, Mohamad; Ganzha, Maria; Paprzycki, Marcin (Amsterdam : IOS Press)
Includes bibliographical references and indexes